Effect of acetazolamide on physiological changes in fifteen-year olds at high altitude - Thompson, Sarah. (2008)
Determine the physiological effect of high altitude (HA) and the effect of the carbonic anhydrase inhibitor, acetazolamide (act.) on 15-year olds.